Early life exposure to unpredictable parental sensory signals shapes cognitive development across three species - Davis, Elysia Poggi; McCormack, Kai; Arora, Hina; Sharpe, Desiree; Short, Annabel K.; Bachevalier, Jocelyne; Glynn, Laura M.; Sandman, Curt A.; Stern, Hal S.; Sanchez, Mar; Baram, Tallie Z. (Frontiers in Behavioral Neuroscience, 2022)
Exposure to early life adversity has long term consequences on cognitive function. Most research has focused on understanding components of early life adversities that contribute to later risk, including poverty, trauma, maltreatment, and neglect. Whereas these factors, in the aggregate, explain a significant proportion of emotional and cognitive problems, there are serious gaps in our ability to identify potential mechanisms by which early life adversities might promote vulnerability or resilience. Here we discuss early life exposure to unpredictable signals from the caretaker as an understudied type of adversity that is amenable to prevention and intervention. We employ a translational approach to discover underlying neurobiological mechanisms by which early life exposure to unpredictable signals sculpts the developing brain. First, we review evidence that exposure to unpredictable signals from the parent during sensitive periods impacts development of neural circuits. Second, we describe a method for characterizing early life patterns of sensory signals across species. Third, we present published and original data illustrating that patterns of maternal care predict memory function in humans, non-human primates, and rodents. Finally, implications are discussed for identifying individuals at risk so that early preventive-intervention can be provided.